Defining Public Will. Issue 1 (February 2014) - Raile, Eric D.; Raile, Amber N. W.; Salmon, Charles T.; Post, Lori Ann
<x xml:space="preserve">Abstract</x> Scientific elaboration of "public will" would enhance the concept's analytical usefulness and contribute to improved understanding in various fields, including political science and public policy. Previous work has utilized the term but has jumped the crucial stage of formally defining public will as a conceptual variable. This project constructs a definitional system that breaks the concept into components and offers operationalizations and assessment targets. Analysis begins with consideration of social systems and their direct ties with other definitional components like shared recognition of the problem and of proposed means of addressing the problem. Resolve to address the situation and to sustain collective action are also essential components. The project then applies the definitional system through a brief case study of firearm control and considers various scholarly implications. The definitional system emphasizes the simultaneous existence of multiple "publics" and argues against using public will synonymously with majority public opinion.